Penerapan Undang-Undang Cipta Kerja dan Undang-Undang Perlindungan Anak Bagi Pekerja Anak di Sektor Industri - Abdul Rahman; Sri Karmila Dol (Sekolah Tinggi Agama Islam Negeri Majene, 2023)
The issue of child labor has been widely highlighted and has become a national and even international issue that must receive serious attention from the government and society, because it has a negative impact on the nation’s future generations. The (weak) economic situation has forced children to help their parents earn a living to meet the family’s economic needs, or at least to meet their own needs. This research aims to determine the implementation of job creation laws and child protection laws against the exploitation of child labor as well as the obstacles in overcoming the exploitation of child labor in the industrial sector. This research is empirical legal research with data sources (informants) from government officials, company owners and child workers. In providing protection against child labor, the government strictly enforces Minister of Manpower regulation no. Per.01/Men/2003 and its implementing regulations. Obstacles to the protection of child labor in the industrial sector include: 1) non-implementation of the mandate of the 1945 Constitution, 2) low level of legal awareness by employers, there is no mechanism for dealing with child labor in companies and there is no model for solving child labor problems.